2013
DOI: 10.4236/jsea.2013.611068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Internet Advertisement and Its Features on E-Commerce Retail Sales: Evidence from Europe

Abstract: The stimulus to carry out this research is to investigate the relationship between internet advertisement and its features on the total E-commerce sales of the top five countries of Europe. The units of analysis are the individuals of UK, France, Italy, Germany and Netherland. Secondary data are collected from the reports of [1] (ADEX, 2010) and [2] (Eurostats, 2011). To empirically determine the relationship between independent variable and dependent variable in the European context, the study uses various st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The internet evolution and revolution have brought dramatic changes in the business world. Conducting business is just a matter of a second; you can do it by simply clicking a button (Harfoushi, Alfawwaz, Obeidat, Obeidat & Faris, 2013). Online advertising is referred to as the promotion of products, services, brands, or a company on the internet (Priyanka, 2012;Singh, 2016).…”
Section: Concept Of Online Advertisementmentioning
confidence: 99%
“…The internet evolution and revolution have brought dramatic changes in the business world. Conducting business is just a matter of a second; you can do it by simply clicking a button (Harfoushi, Alfawwaz, Obeidat, Obeidat & Faris, 2013). Online advertising is referred to as the promotion of products, services, brands, or a company on the internet (Priyanka, 2012;Singh, 2016).…”
Section: Concept Of Online Advertisementmentioning
confidence: 99%
“…An empirical research about e-commerce performance of corporations in China has been presented, and results have shown that e-commerce application has a positive effect on income increase [39]. Similarly, in [40], authors conducted a research in five EU countries (the United Kingdom, Germany, France, the Netherlands and Italy) with the aim of defining the impact of internet advertising on e-commerce in the EU. The research was done using information collected between 2001 and 2010, and it showed that investment in online advertisement generates better sales.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…To determine the buying behavior online client's moves to online advertisement, In addition the study also plans to settle the impacts of online advertising affects emotionally and provisional respond on buying behavior of online products. (Harfoushi, Alfawwaz, Obeidat, Obiedat, & Faris, 2013) Suggested that the concept of online shopping culture are increased rapidly worldwide. Furthermore the customers buying a product online they have the facility to get the best services only by a simple click which becomes very comfortable for the people.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason of this will be discussed here that is loss of trust is one of the most ordinary indications for buyers not to buy from the internet. (Harfoushi et al, 2013) Explained that the online advertisement captured the overall internet market for which these facts the big online companies in the world are makes a different strategies for the accurate measure and calculated estimation to knows about the future online business requirements standing on the internet floor they basic purpose of this strategy is to make a future classification the customers which they response their online products or not. The online companies in the world they working for the exact planning and makes a strategies for the expansion of retailing on the internet this is because it provide the facility to the consumers to buy a product easily and feels very comfortable with their specific online website.…”
Section: Introductionmentioning
confidence: 99%